Pengaruh Status Sosial Ekonomi Terhadap Uang Japuik di Kabupaten Padang Pariaman - Roza Witri Sulistiani; Idris Idris (Jurnal Kajian Ekonomi dan Pembangunan, 2021)
This study attempts to influence the estimate and explains work, the number of income and education to money japuik in Padang Pariaman District, the type research this  research is descriptive the data used was primary and secondary data that analyzed using multiple linear regression. The estimation results shows that the type of work  has a significant  influence on the amount of money japuik in Padang Pariaman District, the number of income is significantly positive effect on money japuik in Padang Pariaman District and Education also has a positif but not significant effect on japuik money in Padang Pariaman district.